Study of the Impact of Various Abrasive Factors on the Microrelief of the Surface of Hybrid Ceramic Orthopedic Structures - Kozhemov S.I., Nikonova A.V, Sevbitov A.V., Enina Yu.I, Dorofeev A.E, Kamenskov P.E., (Opción, 2019)
The aim of the study is to investigate the impact of various abrasive factors on the microrelief of the surface of hybrid ceramic orthopedic structures. A laboratory study was conducted with the optical Profiler S neox (Sensofar, Spain) as a method. As a result, gradual abrasive wear leads to the loss of dry shine of the surface of hybrid ceramic crowns. In conclusion, Processing cleaning powders of various degrees of abrasiveness in the process of conducting professional hygiene of the oral cavity cause abrasive wear of the surface of the hybrid ceramic crowns.